LncRNA H19 as a Competing Endogenous RNA to Regulate AQP Expression in the Intestinal Barrier of IBS-D Patients - Chao, Guanqun; Wang, Zhaojun; Yang, Yi; Zhang, Shuo (Frontiers in Physiology, 2021)
Objective: The study aimed to investigate the role of Long non-coding RNA (LncRNA) H19 in the pathogenesis of Diarrhea Irritable Bowel Syndrome (IBS-D), and further to the regulatory effect of LncRNA H19 on AQP1, 3 in the intestinal mucosa of IBS-D patients, so as to seek a new way to elucidate the mechanism of IBS in clinic. Methods: The levels of LncRNA H19, AQP1, and AQP3 were detected in colonic tissues of IBS-D patients, compared with that in healthy controls. Through RNA gene interference and activation methods, small activating RNA (saRNA) and small interfering (siRNA) were transfered into Caco-2 cells in vitro experiment, and sub-group for two control group, siH19 empty vector group, siH19 interference group, overexpression H19 vector group, and overexpression H19 empty vector group. Quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) and Western blot were applied to evaluate the expression levels of LncRNA H19 and the amount of AQP1 and AQP3 protein expression, respectively. Results: Compared with healthy volunteers, the levels of LncRNA H19, AQP1, and AQP3 in the colonic mucosa of IBS-D patients were significantly decreased (P < 0.05). The results in vitro transfection experiment revealed that the level of LncRNA H19 in the siH19 interference group was significantly declined (P < 0.05), while there was a remarkable increase in the overexpression H19 vector group (P < 0.05), compared with the corresponding control groups. The expression of AQP1 and AQP3 in Caco-2 cells was of positive correlation with the level of LncRNA H19. Conclusion: That the down-regulation of LncRNA H19 resulted in the expression changes of AQP1 and AQP3 may play an important role in the occurrence and development of IBS-D.